Blockchain attributes in Malaysia: a qualitative approach / Arfah Aisyah Ahmad Sabri, Sharina Tajul Urus and Noraizah Abu Bakar - Ahmad Sabri, Arfah Aisyah; Tajul Urus, Sharina; Abu Bakar, Noraizah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
With a plethora of benefits and innovations, many companies across the world are considering the adoption of blockchain technology for their businesses. Blockchain enables the storage of all transactional data and shared files among participants across the network, regardless of multiple locations or geographical dispersion. Despite blockchain's growth and tremendous demand, little is known about the attributes of blockchain, especially from a finance perspective. Thus, this paper aimed to investigate the blockchain attributes of a Malaysian organisation. This study employed a qualitative method by utilising the case study approach. The interviews were guided by the research objectives, and the data was analysed using thematic coding. The proposed research outcome from this research is in the form of a Blockchain Attributes Taxonomy Model. From a practical point of view, the proposed model will offer some insight to practitioners like accountants and auditors. They may apply their technical competence and know-how more effectively during the deployment of blockchain with an understanding of the attributes themselves to take advantage of the numerous benefits offered by blockchain innovation. For the practitioner, they could carefully evaluate the nature of blockchain in optimising the organisation's capabilities to remain competitive in the market.